2008
DOI: 10.1086/524146
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decline of Influenza Vaccine–Induced Antibody in the Elderly: Is It Real, or Is It Relevant?

Abstract: Advisory committees have cautioned that influenza vaccine-induced antibody declines more rapidly in the elderly, falling below seroprotective levels within 4 months. We conducted a literature review to assess this assertion. The articles that were included in this review reported antibody levels > or =4 months after influenza immunization in persons > or =60 years old, interpretable in the context of annual influenza vaccine-approval criteria (seroprotection/seroconversion) specified by the Committee for Propr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 55 publications
12
89
2
3
Order By: Relevance
“…5 Few other studies of ADV have included extended follow-up serology but Ruf et al 38 also reported no advantage in seroprotection rates for ADV over TIV, 4 and 8 mo after vaccination of German seniors. The tendency for protective titers to persist for 6 mo and longer after TIV in elderly adults was highlighted in a recent literature review 39 and is important for season-long protection against influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…5 Few other studies of ADV have included extended follow-up serology but Ruf et al 38 also reported no advantage in seroprotection rates for ADV over TIV, 4 and 8 mo after vaccination of German seniors. The tendency for protective titers to persist for 6 mo and longer after TIV in elderly adults was highlighted in a recent literature review 39 and is important for season-long protection against influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is not a new observation and is supported by other studies. 11 The fact that we measured antibody persistence beyond one season is unique to our study. Our findings indicate that antibody to influenza B virus is least persistent after vaccination waning from 100% after the first year to between 50-16% the second year.…”
Section: Discussionmentioning
confidence: 99%
“…anti-HA antibody responses induced in previously unvaccinated persons) had been noted in older adult populations compared to younger adults in two reviews (Goodwin et al, 2006;Beyer et al, 1989). However, both approaches highlight serious methodological flaws which include a failure to exclude participants with (i) conditions that have influence on the immune system; (ii) those previously vaccinated and (iii) those with high pre-vaccination titers (Skowronski et al, 2008) (see below).…”
Section: What Are the Estimates Given From Observational Clinical Andmentioning
confidence: 99%
“…Although the early decrease in protective anti-HA antibody levels (within 4 months following vaccination) is frequently raised as a concern with respect to the timing of vaccination of elderly individuals (Smith et al, 2006), a recent review conducted by Skowronski et al (2008) suggests this may not be an issue. Amongst the 14 studies included in this review, 8 reported seroprotection rates (Ruf et al, 2004;MacKenzie, 1977;Peters et al, 1988;Delafuente et al, 1998;Buxton et al, 2001;Brydak et al, 2003;Praditsuwan et al, 2005;Hui et al, 2006) and 6 seroconversion rates alone (McElhaney et al, 1993;Powers et al, 1995;Van Hoecke et al, 1996;Minutello et al, 1999;Mysliwska et al, 2004;Keylock et al, 2007).…”
Section: Is the Protective Hai Titre Decline Throughout The Influenzamentioning
confidence: 99%